The relevance of an optimal policy mix in the CEMAC zone - Jean C. Kouam; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The study analyses the nature of the nexus between budget deficit and economic growth given inflation trends. It focuses on data from the six CEMAC countries for the period 2000 to 2021. The employs unit root tests and the generalized method of moments (GMM) for the empirical evidence. The following results are established: (i) the level of inflation above and below which the nexus between budget deficit and economic growth changes sign is about 1.8%. (ii) Below this threshold, each 1% decrease in budget deficit induces an increase in economic growth of about 0.30%; but above the threshold, economic growth decreases by 1 % when budget deficit increases by 0.08%. In view of the war in Ukraine and the global economic situation, which require countries to take adequate measures to strengthen the resilience of their economies, including through high-impact economic activities, any national policy aimed at reducing the budget deficit should be preceded by the reduction of inflation to below 1.8%. Otherwise, any measures put in place by the monetary authorities to stabilize prices would not have the expected effect on economic growth and would hence, be counterproductive. In terms of theoretical underpinnings, at the inflation threshold, the findings are consistent with the 'Ricardian equivalence' theorem on the absence of any tangible incidence of budget deficits on economic prosperity while above (below) the inflation threshold, the findings are in line with neoclassical economists (Keynesian perspective) on a negative (positive) linkage between budget deficits and economic growth. This study complements the extant studies by providing thresholds at which budget deficit affects economic growth.
Keywords: E23; F21; F30; L96; O55; 330; CEMAC; Inflation; Economic growth; Budget deficits; Non-linear effects